ANALISIS PENGGUNA LAYANAN GO-JEK DIKOTA PALEMBANG - Ery Hartati; Yulistia Yulistia (LPPM STMIK Pringsewu, 2017)
Current technological developments in the field of transportation is very rapid, especially on online transportation. The purpose of this research is to know how far the benefits of go-jek service in Palembang City for the users by knowing the magnitude of the effect of knowing the influence of Perceived Usefulness, Perceived Ease Of Use to the utilization of Go-Jek user service in Palembang city towards the utilization of Go-Jek user service in Palembang city. The research data was collected through observation, questionnaire and interview. By using TAM method (Technology Acceptance Model). The population in this study was 133 respondents, consisting of 46% male respondents and 87% women. The results of the data obtained are then processed using 5 items likert scale statements .., work expectations, high user intentions, multiple regression test results show a very strong relationship between the expectations of vidalable performance, work expectations, each has a positive and significant results (p-value <0.00) of behavioral intentions in using the service of the Project.